THR INFLUENCE OF BRAND AWARENESS, COUNTRY OF ORIGIN, AND PRODUCT INNOVATION TOWARDS CONSUMER ATTITUDE AND HOW THEY AFFECT CONSUMER PURCHASE INTENTION - SUSIANTI, SUSIANTI B1024141009 (Jurnal Manajemen Update, 2019)
ABSTRACTThe development of technology has developed drastically and continues to grow until now and increasingly globally. The development of this technology can be seen through people's lifestyles that began to change along with the emergence of smartphones, and internet networks that can be accessed more easily through each smartphone. The increase in Oppo smartphone sales in Indonesia continues to increase. However, companies need to know and understand consumer behavior towards the products offered. The attitude of consumers is part of the purchasing process. Consumers tend to be aware of and choose the brands that they recognize, and from which countries the products are from, and how innovative the products they will buy. This study aims to analyze consumer attitudes and purchase intention on Oppo smartphone products in Pontianak by using variable brand awareness, country of origin, and product innovation. The sample in this study were 100 respondents aged over 17 years and domiciled in Pontianak. The method of data analysis in this study was the SEMPLS method using SmartPLS version 3.0 software. All hypotheses are accepted which means there is a positive direct effect between variables. This study shows the strongest correlation between consumer attitudes and purchase intention.Keyword: Brand Awareness, Country of Origin, Product Innovation, Consumer Attitude, and Purchase IntentionREFERENCESÂ Aaker, D. A. (1991). Managing Brand Equity â€“ Capitalizing on the Value of a Brand Name. New York: The Free PressAaker, D. A. (2008). Strategic market management. 8th Edition. Chichester: John Wiley.Acharya, C., & Greg, E. (2001). An Examination of Effect of Country of Design and Country of Assembly on Quality Perceptions and Purchase Intentions. Australian Marketing Journal 9 (1).Agbonifoh, B. A., & Jonathan, U. E. (1999). Attitudes of Developing Counties Towards â€œCountry-of-Originâ€ Products in an Era of Multiple Brands. Journal of International Consumer Marketing, 11(4), 97â€“116.Â Barber, N., Pei-Jou, K., Melissa, B., & Raymond, G. (2012). Measuring Psychographics to Assess Purchase Intention and Willingness to Pay. Journal of Consumer Marketing. Vol. 29. NO. 4. 2012. 280â€“292.Boone, H. N., & Deborah, A. B. (2012).Â Analyzing likert data. Journal of extension, 50(2), 1-5.Cateora, P. R., & John L. G. (1999). International Marketing. 10th Edition. Boston, Mass. : Irwin/McGraw-Hill.Cooper, D. R. & Pamela, S. S. (2006). Business Research Methods. Irwin/McGraw-Hill.Dafler, F. (2013). Memahami dan mempelajari SmartPLS.Durianto, D., Sugiarto, & Lie, J. B. (2004). Brand Equity Ten. Jakarta: Gramedia Pustaka Utama.Eom, J. & Cho, Y. C. (2015). Exploring Brand Awareness and Purchase Intention on Complete and Ingredient Brands of Smartphone. Journal of Marketing Thought, Vol.2, 73-84.Fontana, A. (2011). Innovate we can!. Bekasi: Cipta Inovasi Sejahtera.Fu, F. Q. & Michael, T. E. (2013). The Moderating Effect of Perceived Product Innovativeness and Product Knowledge On New Product Adaption An Intergrated Model, Journal of marketing theory and practice, vol 21, no : 3Ghorbani, H., & Madani, F. (2012). The Analysis Of Effective Factors on Product Brand Image After Extension (PBI) in Home Appliance Industry In Iran. African Journal of Business, Vol.6, No : 27Ghozali, I. (2013). Aplikasi Analisis Multivariate Dengan Program SPSS. 2nd Edition. Semarang: BP Universitas Dipenogoro.Grundey, D., & Silwia, B. (2008). Consumers Economics: Brand Awareness Among Polish Consumers. Transformation in Business and Economics, vol 7, No 2(14), Supplement B.Halim, W. Z. W., & Abu, B. A. (2005). Consumer Purchase Intention at Traditional Restaurant and Fast Food Restaurant. ANZMAC Conference: Consumer Behaviour.Hawkins, D., Roger, J. B., & Keneth, A. C. (1980). Consumer Behavior: Building Marketing Strategy, 7th ed., Mc-Graw Hill Company.Hox, J., & Timo, B. (2011). An Introduction to Structural Equation Modeling. Family Science Review, 354-373.IDC Asia-Pacific Quarterly Mobile Phone Tracker and ForceTrend. (2017).Ismail, V. Y., & Zain, E. (2008). Peranan Sikap, Norma Subjektif, dan Perceived Behavioral Control terhadap Intensi Pelajar SLTA untuk Memilih Fakultas. Ekonomi.Jurnal Ekonomi dan Bisnis, Vol. 5 Nomor 3, Desember 08. Kogakusha. TokyoKamus Marketing. (1995). Jakarta, Bumi Aksara.Kim, H. B., & Kim, W.G. (2005). The Relationship Between Brand Equity and Firmsâ€™ Performance in Luxury Hotels and Chain Restaurants. Tourism Management. 26:549-560.Kinnear, T. C., & James, R. T. (1996). Marketing Research. 5th Edition. New York: McGraw-Hill Inc.Kotabe, M. (1990). Corporate Product Policy and Innovative Behavior of European and Japanese Multinationals: An Empirical Investigation. Journal of Marketing, Vol.54, (April, 1990), pp.19-33.Kotler, P. & Kevin, L. K. (2009). Management Marketing. 13th Edition. United States: Pearson.Kotler, P.Â (2000).Â MarketingÂ Management. New Jersey: Prentice Hall Intl, Inc.Kotler, P. (2007). Marketing: An Introduction. United States: Pearson Prentice Hall.Liu, F., Jamie, M., Jianyao, L., & Xiangping, L. (2006). English and Chinese? The Role of Consumer Ethnocentrism and Country of Origin in Chinese Attitudes towards Store Signs. Australasian Marketing Journal (AMJ), 14(2), 5â€“16.Â Lukas, B. A & Ferrell, O. C. (2000). The Effect of Market Orientation on Product Innovation. Journal of the Academy of Marketing Science. Vol. 28, Spring.Marâ€™at. (1982). Sikap manusia perubahan serta pengukurannya. Jakarta: Ghalia, Indonesia.McCarthy, J. E. & William, D. P. (1991). Essentials of Marketing. 5th Edition. Homewood Ill Irwin.Muliana, V.A. (2017). Terkuak, Ini Rahasia China Bisa Jadi Negara Maju di Dunia â€œhttp://www.liputan6.com/bisnis/read/3191579/terkuak-ini-rahasia-china-bisa-jadi-negara-maju-di-dunia.â€Mustari, Abul, R. K., Muhammad A., & Indriaty, I. (2016). Effect Of Marketing Comunications, Brand Equity, Brand Awareness Atitudes And Decision Of Customers PT. Mortgage In South Sulawesi. International Journal Of Scientific and Research Publications, vol. 6, issue 8Newzoo. (2018). Top 50 Countries/Markets by Smartphone Users and Penetration. Accessed from https://newzoo.com/insights/rankings/top-50-countries-by-smartphone-penetration-and-users/Ramadania, Sri, G., & Jamaliah. (2013). Country of Origin Effect and Animosity on The Attitude and Purchase Intention of Foreign Products. Asean Marketing Journals, Vol.5, - No. 1Ramadania, Sri, G., M. Rustami. (2015). Cultural Similarity Ethnocentrism and Product Necessity in Evaluation of Malaysian Products: Indonesian Consumer Perspective. 2nd Global Conference on Business and Social Science-2015.